Can lexical errors inform about word class acquisition in FL?: evidence from greek learners of Spanish as a foreign language - Kiriaki Palapanidi; María Pilar Agustín Llach (Revista de Lingüística y Lenguas Aplicadas, 2014)
This research examines the order of acquisition of words of four different classes: verbs, nouns, adjectives, and adverbs in three different levels of proficiency in the FL. We apply the procedure of Error Analysis to a corpus of written compositions and analyze the interlingual and intralingual lexical errors (formal and semantic) of the Greek students of Spanish as a Foreign Language (SFL). Our results have shown us that there is relationship between the type of word and the production of lexical errors and that the lexical errors present different trend in the different word classes. Additionally, our results lead us to the conclusion that the word class as a stronger predictor of lexical error type than proficiency level.